WORK CONDITIONS AND EMPLOYEES’ PERFORMANCE OF TITO YOGURT COMPANY LIMITED MAKURDI BENUE STATE NIGERIA - UCHERWUHE SAMUEL IGBABEE; AKORGA MAMKPEGA CLEMENT (International Studies Journal)
The study examined the Effect of work condition on employees’ performance of Tito yogurt company limited Makurdi Benue State Nigeria. The study specifically sought to establish the effect of work life balance, workload, and safety standards on employees’ performance in Tito yogurt company limited Makurdi Benue State Nigeria. Descriptive survey research design was adopted and self-administered questionnaire was used as instrument of data collection for the study. The target population was 212 employees of Tito yogurt company limited Makurdi Benue State Nigeria and a sample of 139 was arrived at using Taro Yamana formula. The findings revealed that there is a positive significant effect of work life balance on employees’ performance of Tito yogurt company limited Makurdi Benue State Nigeria. The result also showed a positive significant effect of workload on employees’ performance of Tito yogurt company limited Makurdi Benue State Nigeria. Lastly, findings revealed a positive relationship between safety standards on employees’ performance in Tito yogurt company limited Makurdi Benue State Nigeria. The study recommended amongst others that management of Tito yogurt company limited Makurdi Benue State Nigeria should strike a balance between work and personal life for employee well-being to make employees think outside the box and contribute new ideas when they feel encouraged and valued.